Undifferentiated State Induced by Rb‐p53 Double Inactivation in Mouse Thyroid Neuroendocrine Cells and Embryonic Fibroblasts. (23rd April 2015) - Kitajima, Shunsuke; Kohno, Susumu; Kondoh, Atsushi; Sasaki, Nobunari; Nishimoto, Yuuki; Li, Fengkai; Abdallah Mohammed, Mohammed Salah; Muranaka, Hayato; Nagatani, Naoko; Suzuki, Misa; Kido, Yukiharu; Takahashi, Chiaki
Abstract: Retinoblastoma tumor suppressor protein (RB) is inactivated more frequently during tumor progression than during tumor initiation. However, its exact role in controlling the malignant features associated with tumor progression is poorly understood. We established in vivo and in vitro models to investigate the undifferentiated state induced by Rb inactivation. Rb heterozygous mice develop well‐differentiated thyroid medullary carcinoma. We found that additional deletion of Trp53, without change in lineage, converted these Rb‐deficient tumors to a poorly differentiated type associated with higher self‐renewal activity. Freshly prepared mouse embryonic fibroblasts (MEFs) of Rb −/− ; Trp53 −/− background formed stem cell‐like spheres that expressed significant levels of embryonic genes despite of lacking the ability to form colonies on soft agar or tumors in immune‐deficient mice. This suggested that Rb‐p53 double inactivation resulted in an undifferentiated status but without carcinogenic conversion. We next established Rb −/− ; N‐ras −/− MEFs that harbored a spontaneous carcinogenic mutation in Trp53 . These cells (RN6), in an Rb‐dependent manner, efficiently generated spheres that expressed very high levels of embryonic genes, and appeared to be carcinogenic. We then screened an FDA‐approved drug library to search for agents that suppressed the spherogenic activity of RN6 cells. Data revealed that RN6 cells were sensitive to specific agents including ones those are effective against cancer stem cells. Taken together, all these findings suggest that the genetic interaction between Rb and p53 is a critical determinant of the undifferentiated state in normal and tumor cells. Stem Cells   2015;33:1657–1669